Toward optimal prosthetic strategies: the biomechanical impact of design and material in posterior implant-supported fixed partial denture - Karina Mutiara Kasih Suwarno; Ricca Chairunnisa; Syafrinani (Indonesian Journal of Prosthodontic, 2026)
ABSTRACT Implant-supported fixed partial dentures (iFPDs) are used for posterior rehabilitation. Biomechanical problems arise in the posterior due to complicated occlusal stresses and insufficient bone support. Prosthetic design and material stiffness affect stress distribution on peri-implant bone and components, affecting iFPD success. This systematic review examined the biomechanical performance of zirconia, PEKK, and PEEK two- and three-unit iFPDs with fixed-fixed and cantilever designs. FEA was used to evaluate stress distribution and clinical implications. PICO criteria and Boolean operators were used to search PubMed, Scopus, ScienceDirect, and MyEBSCO for 2020–2025 studies. Five of 158.353 documents met PRISMA 2020 criteria. Von Mises stress, prosthesis configurations, material stiffness, and stress concentration zones were extracted. Cantilever designs had the highest stress values, especially at the connector and prosthesis-abutment interface. Due to its stiffness, zirconia shielded the peri-implant bone, while PEKK and PEEK reduced prosthesis stress but transferred more stress to the bone. Connectors were the most biomechanically susceptible in all designs and materials. The synergistic interplay between prosthetic design, material mechanical properties, and loading direction determines the stress distribution pattern and long-term stability of implant-supported prosthetic structures. Keywords: Stress distribution, zirconia, high-performance polymers, finite element analysis, implant-supported fixed partial denture